Aplikasi Pengukuran Kinerja Layanan Perpustakaan berdasarkan ISO 11620:2008 - Fanisya Alva Mustika; Yuni Wibawanti; Retno Suwiyanti (Universitas Indraprasta PGRI Jakarta, 2022)
Libraries as institutions that manage documents and information services need to be handled professionally by following professional methods and standards. The performance of a library is reflected in its service to users. Therefore, the library needs to always improve the services provided to meet user expectations. To make it easier to measure performance, it is necessary to have an application that processes data and produces reports on the performance of library services. The purpose of this research is to produce an application to measure the performance of library services based on ISO 11620:2008. Applications are made using the Java programming language. From the results of performance measurement, the highest performance value on the user satisfaction indicator is 0.768 and the lowest is on the per capita library staff indicator. The total value of library service performance is 2,142 in the low category.